The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/proteomes3040347
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic Oligosaccharide-Degrading Proteome of Butyrivibrio Proteoclasticus

Abstract: The growth and productivity of ruminants depends on a complex microbial community found in their fore-stomach (rumen), which is able to breakdown plant polysaccharides and ferment the released sugars. Butyrivibrio proteoclasticus B316T is a Gram-positive polysaccharide-degrading, butyrate-producing bacterium that is present at high numbers in the rumen of animals consuming pasture or grass silage based diets. B316T is one of a small number of rumen fibrolytic microbes capable of efficiently degrading and utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
(102 reference statements)
0
6
1
Order By: Relevance
“…These unique species may have an association with host metabolism and disease and should be caught on attention. For example, the genus Butyrivibrio has been regarded as a key bacterium in polysaccharide degrading and butyrate producing [ 29 ], however, it was not detected in GDM group.…”
Section: Resultsmentioning
confidence: 99%
“…These unique species may have an association with host metabolism and disease and should be caught on attention. For example, the genus Butyrivibrio has been regarded as a key bacterium in polysaccharide degrading and butyrate producing [ 29 ], however, it was not detected in GDM group.…”
Section: Resultsmentioning
confidence: 99%
“…Butyrivibrio species have Gram-positive cell wall structures (21), and monosaccharide transport across the bacterial cell wall is mediated by a variety of extracellular SBPs linked to dedicated sugar ABC transporter systems (19, 20). Recent data on the B316 T secretome (44, 46) and carbohydrate-transport-associated membrane proteins (45), as well as genome sequence analysis of MB2003 (19, 20), identified a large number of sugar-specific ABC transporter SBPs. Overall, analysis of MB2003 upregulated SBPs and their functional domains, along with surrounding genes encoding polysaccharide-degrading enzymes, revealed that the most prevalent functional category was the COG1653 domain, which is known to be associated with oligosaccharide transport (45).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrivibrio have Gram-positive cell wall structures (10-12), and monosaccharide transport across the bacterial cell wall is mediated by a variety of extracellular SBPs linked to dedicated sugar ABC transporter systems. Recent data on the B316 T secretome (34, 36) and carbohydrate transport-associated membrane proteins (35), as well as genome sequence analysis of MB2003 (10, 11), identified a large number of sugar-specific ABC transporter SBPs.…”
Section: Discussionmentioning
confidence: 99%